Method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using sintering process
By covering the glass phase material and LLZO fine particles on the surface of NCM positive particles, and the outer coating of nano -carbon pipes and amylococcal carbon, solve the problem of positive granular interface and low electronic conduction rate, and achieve higher Battery performance and lower cobalt.
Patent Information
- Application Number
- CN202411356046.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-06-05
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-27
AI Technical Summary
The interface of the positive electrode particles in the prior art is prone to side reactions, resulting in a decrease in service life and low electron conductivity, and poor overall battery performance.
The sintering process is used to cover the glass phase material on the surface of the NCM positive particle, and the LLZO fine particles are used to cover the NCM large particles.
The interface impedance is reduced, the interface side -by -side reaction is reduced, the power charging and discharge performance is improved, the integrity of the electronic conduction path is enhanced, the stability of the overall positive pulp is improved, thereby reducing the amount of cobalt.
Smart Images

Figure CN119340321A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of positive electrode materials, and in particular to a method for manufacturing NCM positive electrode particles coated with LLZO and a glass phase by using a sintering process. Background Art
[0002] The battery is mainly formed by placing the positive electrode and the negative electrode in the electrolyte. The positive electrode is a plurality of positive electrode conductive units (positive electrode materials, such as lithium cobalt oxide) mixed and dispersed in the slurry. Generally speaking, the positive electrode conductive unit must be mixed with the conductive slurry before it can be applied to the electrode sheet and assembled into a battery. Therefore, the numerous positive electrode conductive units (positive electrode materials) are connected to each other through the conductive slurry, so the conductive slurry must have conductive properties or conductivity, so that free electrons can migrate in different positive electrode conductive units without consuming too much energy due to internal resistance, and achieve the purpose of effective conduction. Therefore, when manufacturing the slurry, it is necessary to consider the use of specific conductive materials to adjust the conductivity of the slurry.
[0003] Generally, in order to increase the conductivity, a plurality of positive electrode particles are filled in the positive electrode slurry, wherein the material of the positive electrode particles can be selected from NCM (lithium nickel cobalt manganese oxide), LMFP (lithium iron manganese phosphate), etc. or a mixture thereof, and the positive electrode particles are distributed in the positive electrode slurry. However, the interface of the positive electrode particles in the prior art is prone to side reactions, which reduces the service life of the positive electrode, and the electronic conductivity is low, so the overall battery performance is poor.
[0004] Based on the long-term experience in battery materials, the applicant hopes to propose a new design. In order to further improve the conductivity of the entire slurry, carbon nanotubes and nano-level amorphous carbon are added to coat the positive electrode particles in the positive electrode material of the battery to improve the conductivity of the entire positive electrode. In addition, the glass phase material is coated on the surface of the positive electrode particles, thereby reducing the interface impedance; improving the powder coating and stabilizing it in the electrolyte to prevent interface side reactions.
[0005] Therefore, the prior art has defects and needs to be improved. Summary of the invention
[0006] The purpose of the present invention is to solve the problems in the above-mentioned prior art. The present invention proposes a method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process. The method coats the glass phase material on the surface of the NCM large particles to form a glass phase layer. The glass phase layer can prevent the direct contact between the NCM large particles and the electrolyte, and reduce the interface side reaction; at the same time, the interface impedance of lithium ions entering and exiting the NCM large particles is reduced, the rate charge and discharge performance is improved, and the existence of the glass phase layer can accommodate the volume change of charge and discharge, improve the mechanical properties of the powder, and reduce breakage. And a large number of LLZO fine particles are used to coat the NCM large particles. These LLZO fine particles have the ability to accommodate and evenly flow lithium ions. Therefore, when lithium ions pass through the positive electrode, the path of lithium ions can be dispersed with the guidance of the dispersed LLZO fine particles, so that the positive electrode design can allow lithium ions to have a better path. In addition, nanocarbon tubes and nano-scale amorphous carbon are coated on the outer side of the NCM large particles coated with LLZO fine particles. In this way, electrons can be conducted on the composite NCM large particles, and each nanometer-scale amorphous carbon can be filled in the gaps formed by the interlacing of multiple nano-carbon tubes to form a more complete electron conduction path. The structure of the present invention can provide stability for the overall positive electrode slurry structure, thereby reducing the amount of cobalt used.
[0007] To achieve the above object, the present invention proposes a method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process. The positive electrode particles are present in the positive electrode of a solid-state or quasi-solid-state battery. The manufacturing process includes the following steps:
[0008] Step 500: Take NCM (nickel cobalt manganese oxide) material, which is a plurality of NCM large particles; these NCM large particles are in an irregular cubic shape; put the NCM large particles and the glass phase material into a first mixer at the same time, and stir them thoroughly to make the two evenly mixed; the glass phase material has a lithium ion conductivity rate higher than 10 -5 S / cm amorphous solid electrolyte;
[0009] Step 510: then aerobic sintering is performed on the stirred NCM large particles and the glass phase material; after sintering, the NCM large particles are coated with a glass phase layer formed by the glass phase material to form NCM large particles having a glass phase layer; the glass phase layer can prevent the direct contact between the NCM large particles and the electrolyte, reduce the interface side reaction, and at the same time reduce the interface impedance of lithium ions entering and leaving the NCM large particles;
[0010] Step 520: Mixing LLZO (lithium lanthanum zirconium oxide) material with NCM large particles having a glass phase layer, wherein the LLZO material is a plurality of LLZO fine particles; placing the NCM large particles having a glass phase layer and the LLZO fine particles into a second mixer at the same time and stirring them sufficiently, so that the LLZO fine particles are evenly distributed in or on the glass phase layer to form composite NCM large particles;
[0011] Step 530: Then, the composite NCM large particles are subjected to oxygen sintering, and the interface impedance between the LLZO fine particles and the NCM large particles during lithium ion transmission is eliminated by the sintering process; a plurality of sintered powders are formed.
[0012] The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process also includes step 540: mixing the sintered powder, a plurality of CNTs (Carbon Nanotubes) and a plurality of nano-scale amorphous carbons.
[0013] The features and advantages of the present invention may be further understood through the following description, and please refer to the accompanying drawings while reading. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The manufacturing process of the positive electrode particles of the present invention is shown.
[0015] Figure 2 A diagram showing the structure of the positive electrode particles of the present invention.
[0016] Figure 3 A structural diagram showing the positive electrode of the present invention.
[0017] Figure 4 A structural diagram showing the composite NCM large particles of the present invention.
[0018] Figure 5 A structural diagram showing the composite NCM large particles of the present invention.
[0019] Figure 6 A structural diagram showing the composite NCM large particles of the present invention. DETAILED DESCRIPTION
[0020] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0021] The structural composition of the present invention, as well as the effects and advantages it can produce, are described in detail below with reference to a preferred embodiment of the present invention.
[0022] Please refer to Figures 1 to 6 As shown, the method of the present invention for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process is shown.
[0023] like Figure 3 As shown, a positive electrode 100 of a general solid-state or quasi-solid-state battery comprises:
[0024] a positive electrode substrate 10;
[0025] A positive electrode slurry layer 12 is coated on the positive electrode substrate 10, wherein the positive electrode slurry layer 12 comprises:
[0026] A positive electrode slurry 14 containing a binder, wherein the binder is, for example, PVDF (polyvinylidene difluoride), PEO (poly(ethylene oxide)), and the like.
[0027] The positive electrode particles 200 account for 80 wt % to 98 wt % of the positive electrode slurry layer 12 .
[0028] The manufacturing process of the positive electrode particles 200 (please refer to Figure 1 ) includes the following steps:
[0029] Take NCM (nickel cobalt manganese oxide) material, wherein the NCM material is a plurality of NCM large particles 22, wherein the size of a single NCM large particle 22 is 3 microns to 5 microns; it is a single crystal structure (single crystal). The NCM large particle 22 is in an irregular cubic shape.
[0030] Step 500: Place the NCM large particles 22 and the glass phase material into a first mixer 50 (such as a dry mixer: a three-dimensional mixer or a flat roller mixer or a wet mixer: a DC impeller mixer, wherein the wet mixer is added with anhydrous alcohol or isopropanol solvent) and stir them thoroughly to make the two evenly mixed, wherein the rotation speed of the first mixer 50 is 20 rpm to 500 rpm, and the stirring time is 2 hours to 12 hours.
[0031] The glass phase material has a lithium ion conductivity higher than 10 -5 S / cm non-crystalline oxide or non-oxide solid electrolyte. For example: lithium and IIIA, IVA, VA group oxides (such as: Li2O-RO x , R=B (boron), Al (aluminum), Si (silicon), Ge (germanium), P (phosphorus), As (arsenic), etc., x=1 to 3), or an amorphous oxide-based solid electrolyte (such as an amorphous perovskite-based solid electrolyte (LLTO), a garnet-based solid electrolyte (LLZO), or at least one of lithium-phosphorus-oxygen-nitride (LiPON).
[0032] Step 510: Then, the stirred NCM large particle 22 and the glass phase material are subjected to oxygen sintering, wherein the sintering temperature is 250°C to 650°C, the temperature is increased by 1.5°C to 5°C / min, and the temperature is kept at the highest temperature for 0.5 hour to 4 hours. After sintering, the NCM large particle 22 is coated with a glass phase layer 25 formed by the glass phase material, that is, the NCM large particle 250 with a glass phase layer is formed. The thickness of the glass phase layer 25 is between 5 nanometers and 100 nanometers.
[0033] The glass phase layer 25 can prevent the direct contact between the NCM large particles 22 and the electrolyte, reducing the interface side reactions; at the same time, it can reduce the interface impedance of lithium ions entering and exiting the NCM large particles 22, improve the rate charge and discharge performance, and the existence of the glass phase layer 25 can accommodate the volume changes during charge and discharge, improve the mechanical properties of the powder, and reduce breakage.
[0034] Step 520: LLZO (lithium lanthanum zirconium oxide) material (such as Li 6.2 Ga 0.8 La3Zr2O 12 (Gallium-doped lithium lanthanum zirconium oxide)) is mixed with the NCM large particle 250 having a glass phase layer, wherein the LLZO material is a plurality of LLZO fine particles 24, and the maximum radial dimension of a single LLZO fine particle 24 is less than 40 nanometers.
[0035] The NCM large particles 250 with the glass phase layer and the LLZO fine particles 24 are simultaneously placed in a second mixer 52 (such as a three-dimensional mixer or a flat rolling mixer) and stirred sufficiently to make them uniformly mixed, wherein the rotation speed of the second mixer 52 is 20 rpm to 500 rpm, and the stirring time is 2 hours to 12 hours. After stirring, the LLZO fine particles 24 are distributed in the glass phase layer 25 or on the surface of the glass phase layer 25 to form a composite NCM large particle 20 (such as Figure 4 ).
[0036] The LLZO in the LLZO fine particles 24 is preferably selected from at least one of Ga-LLZO (gallium-doped lithium lanthanum zirconium oxide), Cu-LLZO (copper-doped lithium lanthanum zirconium oxide), Ta-LLZO (tantalum-doped lithium lanthanum zirconium oxide), Sr-LLZO (strontium-doped lithium lanthanum zirconium oxide) and Al-LLZO (aluminum-doped lithium lanthanum zirconium oxide).
[0037] Preferably, the LLZO is selected from Cua, Xb-LLZO (copper-doped lithium lanthanum zirconium oxide), X is selected from Ga (gallium), Ta (tantalum), Sr (strontium), Ba (barium), Al (aluminum), where a+b=0.25 to 0.8, a>0.1; the technology of using copper doping in LLZO is quite difficult, but it can make the overall structure more stable, the passage of lithium ions can be smoother, and the sintering speed is increased and the manufacturing cost is relatively cheap. And when the material is exposed to air, the formation of lithium carbonate is reduced. That is, the surface stability of the entire material during sintering is increased.
[0038] In a single composite NCM large particle 20, the total weight of all the LLZO fine particles 24 is between 0.2 wt% and 2 wt% of the weight of the NCM large particle 250 having a glass phase layer.
[0039] Step 530: Then, the composite NCM large particle 20 is subjected to oxygen sintering, wherein the sintering temperature is 550 to 650°C, the temperature is increased by 1.5°C to 5°C / minute, and the temperature is kept at the highest temperature for 0.5 to 2 hours, and the sintering process is used to eliminate the interface impedance between the LLZO fine particles 24 and the NCM large particles 22 during lithium ion transmission; a plurality of sintered powders 40 are formed as a whole. Basically, after sintering, the LLZO fine particles 24 are widened in the lateral dimension along the surface of the NCM large particle 20, and the longitudinal dimension along the radial direction of the NCM large particle 20 is shortened, and the total volume remains unchanged. After sintering, the LLZO fine particles 24 will adhere to the NCM large particles 250 with a glass phase layer to form the composite NCM large particles 20 as a whole.
[0040] The next step is to mix the sintered powder 40, a plurality of CNTs 30 (Carbon Nanotubes) and a plurality of nano-scale amorphous carbons 35 to form positive electrode particles 300 coated with carbon materials. There are two methods, which are described as follows:
[0041] Step 540A: The sintered powder 40, the plurality of CNTs 30, and the plurality of nano-scale amorphous carbons 35 are simultaneously placed in a dry mixer 55 (such as a planetary mixer or a drum mixer) for mixing, so that the CNTs 30 and the nano-scale amorphous carbons 35 cover the composite NCM large particles 20 to form the positive electrode particles 300 (such as the coated carbon material). Figure 1 ). The stirring speed of the dry stirrer 55 is 50 rpm to 500 rpm, and the stirring time is 2 hours to 8 hours.
[0042] The nano-scale amorphous carbon 35 is a super P conductive agent. The size of the nano-scale amorphous carbon 35 is between 20 nanometers and 100 nanometers. Each of the nano-scale amorphous carbon 35 is mainly located between the gaps formed by the interlacing of multiple CNTs 30 (such as Figure 2 The total weight of the nano-scale amorphous carbon 35 accounts for 0.1 wt % to 2 wt % of the weight of the single composite NCM large particle 20 .
[0043] Alternatively, step 530 is followed by step 540B.
[0044] Step 540B: The CNT 30 is first mixed with the sintered powder 40, and then mixed with the nano-scale amorphous carbon 35 to form the carbon-coated positive electrode particles 300. The CNT is first mixed with the sintered powder by dry ball milling or wet ball milling:
[0045] Dry ball milling mixing is to place the CNT 30 and the sintered powder 40 directly into a dry ball mill 57 for ball milling. The rotation speed of the dry ball mill 57 is between 50 rpm and 1000 rpm. The mixing time is between 20 minutes and 12 hours. The ball milling is performed at room temperature to 50 degrees.
[0046] Another mixing method is wet ball milling, which is to disperse the CNT 30 in a dispersant and then place it in a wet ball mill 56 with the sintered powder 40 for wet ball milling. The speed of the wet ball mill 56 is between 50 rpm and 500 rpm, and the mixing time is between 20 minutes and 12 hours. The dispersant is selected from a polar or non-polar non-aqueous organic solvent.
[0047] After the CNT 30 and the sintered powder 40 are mixed by any of the ball milling methods, the nano-scale amorphous carbon 35 is added and mixed, so that the CNT 30 and the nano-scale amorphous carbon 35 cover the composite NCM large particle 20 to form the positive electrode particle 300 of the coated carbon material.
[0048] The CNT 30 includes short-chain CNT 32 and long-chain CNT 34. The length of the short-chain CNT 32 is between 0.5 micrometers and 1 micrometer, and the length of the long-chain CNT 34 is between 3 micrometers and 8 micrometers. The total weight of the CNT 30 accounts for 0.1 wt% to 2 wt% of the weight of the single NCM large particle 22.
[0049] The CNT 30 can form different levels of cross-connections on the composite NCM large particle 20. When more carbon nanotubes 30 are added, the conductivity of the entire composite NCM large particle 20 will be improved. Figure 5 and 6As shown, the short-chain CNT 32 is used to bridge the LLZO fine particles 24 and the NCM large particles 22. The long-chain CNT 34 is used to cover the composite NCM large particles 20. CNT is a very good conductive material. When it is attached to the composite NCM large particles 20, it forms a shape like a ball of wool (such as Figure 2 ).
[0050] The carbon nanotubes 30 (i.e., CNT 30) are used to increase the electronic conductivity, that is, to form conductive bridges around the various LLZO fine particles 24, so that electrons can be conducted on the composite NCM large particles 20. The carbon nanotubes 30 are randomly distributed on the surface of the composite NCM large particles 20. Because the carbon nanotubes have extremely high conductivity, electrons can be conducted between the different LLZO fine particles 24 and the NCM large particles 22 through the carbon nanotubes, thereby increasing the conductivity of the entire positive electrode 100 as a whole.
[0051] The nano-scale amorphous carbon 35 is a conductive agent like the CNT 30. Since the nano-scale amorphous carbon 35 is in the form of particles, and the carbon nanotubes 30 are in the form of long strips, gaps are formed between the criss-crossed carbon nanotubes 30, and these gaps cannot conduct current. Therefore, adding the nano-scale amorphous carbon 35 to the gaps can allow the charge to be conducted to the next carbon nanotube 30 through the bridging of the nano-scale amorphous carbon 35, thereby further increasing the current transmission.
[0052] In the present invention, (the CNT 30 + the nano-scale amorphous carbon 35): the single composite NCM particle 20 = (0.09 to 3): 100 (weight ratio).
[0053] The CNT 30: the nano-scale amorphous carbon 35: a single composite NCM large particle 20 (containing LLZO and NCM large particles with a glass phase layer) = 0.5: 1: 100 (weight ratio).
[0054] After sintering and stirring, the NCM large particles 22 have a size of 3 to 5 microns, the lateral size (i.e., the size along the spherical surface) of the LLZO fine particles 24 is between 50 nanometers and 300 nanometers, and the size of the nano-scale amorphous carbon 35 is between 20 nanometers and 100 nanometers.
[0055] The advantage of using carbon nanotubes in the present invention is that lithium ions can be easily stabilized between the carbon nanotubes, so the positive electrode slurry in the present invention can stabilize a large number of lithium ions, thereby improving the overall conductivity of lithium ions, and electrons can be easily fixed between the short-chain carbon nanotubes, thereby improving the overall conductivity of lithium ions. In addition, because the ion conductivity is very high, it helps the rapid charging and rapid discharging of the entire battery, and can also reduce the amount of cobalt used, thereby reducing the overall production cost.
[0056] The advantages of the present invention are that the glass phase material is coated on the surface of the NCM large particles to form the glass phase layer, and the glass phase layer can prevent the direct contact between the NCM large particles and the electrolyte, and reduce the interface side reaction; at the same time, the interface impedance of lithium ions entering and leaving the NCM large particles is reduced, the rate charge and discharge performance is improved, and the existence of the glass phase layer can accommodate the volume change of charge and discharge, improve the mechanical properties of the powder, and reduce breakage. The NCM large particles are coated with a large number of LLZO fine particles. The LLZO fine particles have the ability to accommodate and evenly flow lithium ions. Therefore, when lithium ions pass through the positive electrode, the path of lithium ions can be dispersed by the guidance of the dispersed LLZO fine particles, so the design of the positive electrode of the present invention can make lithium ions have a better path. The present invention also coats the outer side of the NCM large particles coated with LLZO fine particles with nano-carbon tubes and the nano-scale amorphous carbon. It allows electrons to be conducted on the composite NCM large particles and each of the nano-scale amorphous carbons can be filled in the gaps formed by the interlacing of multiple nano-carbon tubes to form a more complete electron conduction path. The structure of the present invention can provide stability for the overall positive electrode slurry structure, thereby reducing the amount of cobalt used.
[0057] In summary, the humanized and considerate design of the present invention is quite in line with the actual needs. It specifically improves the existing deficiencies and has obvious breakthrough advantages compared with the known technology. It does have the improvement of efficacy and is not easy to achieve. The present invention has not been published or disclosed in domestic and foreign literature and markets, and has complied with the provisions of the Patent Law.
[0058] The above detailed description is a specific description of a feasible embodiment of the present invention, but the embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the technical spirit of the present invention should be included in the patent scope of the present invention.
Claims
1. A method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process, characterized in that: The positive electrode particles are present in the positive electrode of a solid-state or quasi-solid-state battery, and the manufacturing process of the positive electrode particles comprises the following steps: Step 500: Take NCM material, that is, take nickel cobalt manganese oxide lithium material, wherein the NCM material is a plurality of NCM large particles; wherein the NCM large particles are in an irregular cubic shape; place the NCM large particles and the glass phase material into a first mixer at the same time, and stir them sufficiently to make the two uniformly mixed; the glass phase material has a lithium ion conductivity higher than 10 -5 S / cm amorphous oxide or non-oxide solid electrolyte; Step 510: Then, the stirred NCM large particles and the glass phase material are subjected to oxygen sintering; after sintering, the NCM large particles are coated with a glass phase layer formed by the glass phase material, that is, NCM large particles with a glass phase layer are formed; wherein the glass phase layer can prevent the direct contact between the NCM large particles and the electrolyte, reduce the interface side reaction, and at the same time reduce the interface impedance of lithium ions entering and leaving the NCM large particles; Step 520: Mixing the LLZO material with the NCM large particles having a glass phase layer, wherein the LLZO material is a plurality of LLZO fine particles; placing the NCM large particles having a glass phase layer and the LLZO fine particles into a second mixer at the same time and stirring them sufficiently to make them uniformly mixed; after stirring, the LLZO fine particles are distributed in the glass phase layer or on the surface of the glass phase layer to form composite NCM large particles as a whole; the LLZO material is a lithium lanthanum zirconium oxide compound material; Step 530: Then, the composite NCM large particles are subjected to oxygen sintering, and the sintering process is used to eliminate the interface impedance between the LLZO fine particles and the NCM large particles during lithium ion transmission; a plurality of sintered powders are formed as a whole.
2. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 1, characterized in that: in The size of a single NCM large particle is 3 to 5 microns; it has a single crystal structure; The glass phase layer has a thickness between 5 nanometers and 100 nanometers; In step 520, the maximum radial dimension of the LLZO fine particles is less than 40 nanometers.
3. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 1, characterized in that: Wherein in step 500, the first mixer is selected from a three-dimensional mixer or a flat rolling mixer; or a DC impeller mixer; Anhydrous alcohol or isopropanol solvent is added to the DC impeller mixer and stirred sufficiently to make the two solvents uniformly mixed.
4. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 1, characterized in that: The glass phase material has a lithium ion conductivity greater than 10 -5 S / cm non-crystalline oxide or non-oxide solid electrolyte; it is selected from lithium and oxides of groups IIIA, IVA, VA, or at least one of an amorphous oxide-based solid electrolyte, an amorphous perovskite-based solid electrolyte, a garnet-based solid electrolyte, or lithium-phosphorus-oxygen-nitride.
5. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 1, characterized in that: The glass phase material has a lithium ion conductivity greater than 10 -5 S / cm non-crystalline oxide or non-oxide solid electrolyte; it is selected from Li2O-RO x , wherein R is at least one of boron, aluminum, silicon, germanium, phosphorus, and arsenic, and x = 1 to 3; LLTO; LLZO; LiPON; At least one of the above.
6. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 1, characterized in that: In step 510 , the sintering temperature is 250° C. to 650° C., the temperature is increased at a rate of 1.5° C. to 5° C. / min, and the temperature is maintained at the highest temperature for 0.5 hour to 4 hours.
7. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 1, characterized in that: The LLZO in the LLZO fine particles is selected from at least one of gallium-doped lithium lanthanum zirconium oxide compounds, copper-doped lithium lanthanum zirconium oxide compounds, tantalum-doped lithium lanthanum zirconium oxide compounds, strontium-doped lithium lanthanum zirconium oxide compounds and aluminum-doped lithium lanthanum zirconium oxide compounds.
8. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 1, characterized in that: Wherein the LLZO is selected from Cu a X b -LLZO, i.e., copper-doped lithium lanthanum zirconium oxide, X is selected from at least one of gallium, tantalum, strontium, barium, and aluminum, wherein a+b=0.25 to 0.8, and a>0.1; doping LLZO with copper can make the overall structure more stable, the passage of lithium ions can be smoother, and the sintering speed is increased with a relatively low manufacturing cost; and when the material is exposed to air, the formation of lithium carbonate is reduced; that is, the surface stability of the entire material during sintering is increased.
9. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 1, characterized in that: In a single composite NCM large particle, the total weight of all the LLZO fine particles is between 0.2 wt % and 2 wt % of the weight of the NCM large particle having a glass phase layer.
10. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 1, characterized in that: Wherein in step 520, the rotation speed of the second mixer is 20 rpm to 500 rpm, and the stirring time is 2 hours to 12 hours; and In step 530 , the sintering temperature is 550° C. to 650° C., the temperature is increased at a rate of 1.5 to 5° C. / min, and the temperature is maintained at the highest temperature for 0.5 to 2 hours.
11. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 1, characterized in that: The method further includes step 540: The sintered powder, a plurality of CNTs and a plurality of nano-scale amorphous carbons are mixed with a carbon material to form positive electrode particles coated with the carbon material.
12. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 11, characterized in that: The carbon material is mixed in the following manner: the sintered powder, the multiple CNTs and the multiple nano-scale amorphous carbons are simultaneously placed in a dry mixer for mixing, so that the CNTs and the nano-scale amorphous carbons cover the composite NCM large particles to form the positive electrode particles of the coated carbon material; the stirring speed of the dry mixer is 50 rpm to 500 rpm, and the stirring time is 2 hours to 8 hours.
13. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 11, characterized in that: The carbon material is mixed in a manner that: the CNT is first mixed with the sintered powder, and then mixed with the nano-scale amorphous carbon to form the positive electrode particles coated with the carbon material; the CNT is first mixed with the sintered powder by dry ball milling or wet ball milling.
14. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 13, characterized in that: The dry ball milling mixing method is to place the CNT and the sintered powder directly into a dry ball mill for ball milling, the dry ball mill has a rotation speed of 50 rpm to 1000 rpm, the mixing time is between 20 minutes and 12 hours, and the ball milling is performed at room temperature to 50 degrees; Then, the nano-scale amorphous carbon is added and mixed, so that the CNT and the nano-scale amorphous carbon cover the composite NCM large particles to form the positive electrode particles of the coated carbon material.
15. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 13, characterized in that: The wet ball milling mixing method is to disperse the CNT in a dispersant and then place the CNT and the sintered powder in a wet ball mill for wet ball milling. The speed of the wet ball mill is between 50 rpm and 500 rpm, and the mixing time is between 20 minutes and 12 hours. The dispersant is selected from a polar or non-polar non-aqueous organic solvent; Then, the nano-scale amorphous carbon is added and mixed, so that the CNT and the nano-scale amorphous carbon cover the composite NCM large particles to form the positive electrode particles of the coated carbon material.
16. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by sintering process as claimed in claim 11, characterized in that: The size of the nano-scale amorphous carbon is between 20 nanometers and 100 nanometers; each nano-scale amorphous carbon is mainly located between the gaps formed by the interlacing of multiple CNTs; The total weight of the nano-scale amorphous carbon accounts for a proportion of 0.1 wt % to 2 wt % of the weight of a single composite NCM large particle.
17. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 11, characterized in that: The CNTs are short-chain CNTs and long-chain CNTs, the short-chain CNTs are between 0.5 microns and 1 micron in length, and the long-chain CNTs are between 3 microns and 8 microns in length; the short-chain CNTs are used to bridge the LLZO fine particles and the NCM large particles; the long-chain CNTs are used as a whole to cover the composite NCM large particles.
18. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 11, characterized in that: The proportion of the total weight of the CNT to the weight of a single composite NCM large particle is between 0.1wt% and 2wt%.
19. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 11, characterized in that: Wherein, (the CNT+the nano-scale amorphous carbon):single composite NCM particle=(0.09 to 3):100, which is a weight ratio.
20. The method for manufacturing NCM positive electrode particles coated with LLZO and glass phase by using a sintering process as claimed in claim 11, characterized in that: The CNT: the nano-scale amorphous carbon: the single composite NCM large particle = 0.5:1:100, which is a weight ratio.
Citation Information
Patent Citations
Lithium ion battery cathode material and preparation method thereof and lithium battery
CN110767896A
Spherical ternary composite positive electrode material of lithium ion battery and preparation method thereof
CN112366295A
Spherical ternary composite positive electrode material for lithium ion battery and preparation method of spherical ternary composite positive electrode material
CN114551876A
Garnet type solid electrolyte with glass grain boundary and preparation method of garnet type solid electrolyte
CN116683020A
Solvent-free processing of lithium lanthanum zirconium oxide coated-cathodes
US20220025502A1